Predictors of vitamin D-containing supplement use in the Australian population and associations between dose and serum 25-hydroxyvitamin D concentrations - Black, Lucinda; Jacoby, P.; Nowson, C.; Daly, R.; Lucas, R. (MDPI Publishing, 2016)
© 2016 by the authors; licensee MDPI, Basel, Switzerland.Despite concerns about vitamin D deficiency in the Australian population, little is known about the prevalence and predictors of vitamin D-containing supplement use. We described the use of vitamin D-containing supplements, and investigated associations between supplemental vitamin D intake and serum 25-hydroxyvitamin D (25(OH)D) concentrations, using a single 24-h dietary recall from the 2011–2013 Australian Health Survey (n = 12,153; ages = 2 years). Multiple regression models were used to investigate predictors of vitamin D-containing supplement use in adults, and associations between dose and serum 25(OH)D concentrations/vitamin D sufficiency (=50 nmol/L), adjusting for potential confounders. The prevalence of vitamin D-containing supplement use was 10%, 6% and 19% in children, adolescents and adults, respectively. Predictors of vitamin D-containing supplement use in adults included being female, advancing age, higher educational attainment, higher socio-economic status, not smoking, and greater physical activity. After adjusting for potential confounders, a 40 IU (1 µg) increase in vitamin D intake from supplements was associated with an increase of 0.41 nmol/L in serum 25(OH)D concentrations (95% CI 0.35, 0.47; p < 0.001). However, the prevalence of vitamin D-containing supplement use was generally low in the Australian population, particularly for single vitamin D supplements, with most supplement users obtaining only low levels of vitamin D from other supplement types.